Predictive factors of family health management for caring toddlers with acute respiratory infections - Eka Yulianita, Marisna; Yulia Kasma, Andi; Ayumar, Andi (Jurnal Ners, 2023)
Introduction: Poor air quality due to air pollution, unhealthy lifestyle, and easily transmittable viruses further increases the incidence of acute respiratory infections, especially in toddlers. This study aimed to determine the predictive factors, namely knowledge, attitude, and anxiety, of family health management in preventive and curative areas for caring toddlers with acute respiratory infections. Methods: This type of research is correlational predictive. The sample was mothers who have toddler with a history of ARI. A total of 392 mothers were involved and selected using purposive sampling. The instrument used was a questionnaire of knowledge, attitudes, anxiety, and family health management. Bivariate data analysis used the chi-square test and multivariate analysis used the logistic regression test. Results: Bivariate analysis showed that there was a relationship between knowledge, attitudes, and anxiety with family health management (p-value=0.000). Multivariate analysis showed that variables significantly related to family health management were knowledge (OR=19.791; 95% CI=10.349 to 37.847), attitude (OR=9.265; 95% CI = 3.969 to 21.628), and anxiety (OR=0.137; 95% CI = 0.066 to 0.285). Conclusions: Good knowledge and positive attitudes were related to effective family health management in the care of toddlers with acute respiratory infections. Furthermore, an increase in anxiety will reduce the effectiveness of family health management in the care of toddlers with ARI. Nurses need to optimize the role of the family through health education that focuses on increasing the mother's knowledge and attitudes in family health management, as well as managing anxiety in caring for children with ARI.